Ecotoxicological Evaluation of Poly(epsilon-Caprolactone) Nanocapsules Containing Triazine Herbicides - Clemente, Z.; Grillo, R. [UNESP]; Jonsson, M.; Santos, N. Z. P.; Feitosa, L. O.; Lima, R.; Fraceto, L. F. [UNESP] (Amer Scientific Publishers, 2014)
The triazine class of herbicides includes the compounds ametryn, atrazine, and simazine, which are used to control weeds in plantations of crops such as maize, sorghum, and sugar cane. Despite their acceptance in agriculture, these herbicides can be dangerous to the environment, depending on their toxicity, the degree of contamination, and the duration of exposure. Controlled release systems are increasingly used to mitigate problems of toxicity and minimize environmental impacts, and can also increase herbicide efficiency. The objective of this work was to prepare poly(epsilon-caprolactone) nanocapsules containing ametryn and atrazine, and evaluate their toxicity to aquatic organisms as well as in cytogenetic tests employing human lymphocyte cultures. The PCL nanocapsules were prepared according to the interfacial deposition of pre-formed polymer method. Ecotoxicological assays were performed with the alga Pseudokirchneriella subcapitata and the microcrustacean Daphnia similis. The cytogenetic tests consisted of observing mitotic index alterations after exposing lymphocyte cell cultures to different formulations. Encapsulation of the herbicides in the nanocapsules resulted in lower toxicity to the alga and higher toxicity to the microcrustacean, compared to the herbicides alone. The cytogenetic tests showed that formulations of nanocapsules containing the herbicides were less toxic than the herbicides alone. The findings indicate the potential of the nanocapsule formulations in agricultural applications, where they could help to reduce the quantities of herbicides used as well as impacts on the environment and human health.
Keywords: Environmental Chemistry; Triazine Herbicides; Polymeric Nanoparticles; Genotoxicity; Ecotoxicology